Comparative sustainibilty evaluation on regenerated industrial nickel-cadmium battery based on life-cycle assessment method - Paya Martin, Marilyn (2022)
Nowadays, rapid growth of used rechargeable batteries such as Nickel-Cadmium (NiCd) battery in industries has its own prominent role in certain niche applications. Examples of such applications are in emergency backup, telecommunications and electrical vehicles (EV). Therefore, the evaluation on the performance characteristics of Ni-Cd battery using regeneration method is discussed in this study. Meanwhile, the evaluation on the battery waste management using Life Cycle Assessment (LCA) method and Life Cycle Cost Assessment (LCCA) method on Ni-Cd battery for environmental impact analysis is presented in this study. Principally, the performance of the Ni-Cd battery deteriorates with time due to the process of charging and discharging during the usage of the Ni-Cd battery where crystalline formed on the surface of the battery plate. Hence, high current pulses technique is selected as battery regeneration process (de-crystallization) to break the formed crystalline to recover back the capacity loss and enhanced the performance of Ni-Cd battery. The results show that, the capacity of the Ni-Cd battery increased up to 22% of its capacity after the de-crystallization take place by injecting high current pulses. For Ni-Cd battery waste management, recycling method and battery regeneration method are selected as ways to dispose Ni-Cd battery waste. Therefore, the impact of the selected method for used Ni-Cd battery waste disposal in terms of percentage carbon footprint and cost involved using LCA and LCCA method respectively is evaluated by using SimaPro software. The selected system boundary for the study is gate to gate. Based on the obtained results, it is shown that battery regeneration method is more environmental friendly and economic which produce 24% of carbon footprint and can save up to 87% of process cost and environmental cost than recycle method. Lastly, this study also presented a proposal on the management of the battery waste in order to improve the current way of the battery disposal management and guidance for future works.